Teacher Engagement and Student Achievement in Master’s Program: Faculty of Education, Tribhuvan University (Pragyaratna प्रज्ञारत्न, 2025)
In modern educational organizational research and practice, teacher engagement has emerged as a key area of concern, propelling initiatives to match teacher motivation with strategic objectives. To increase involvement, improve performance, and ensure long-term sustainability, educational institutions all around the world are implementing a variety of interventions. The purpose of the study is to explore the influence of teacher engagement and its key aspects on student achievement in master’s programs at the Faculty of Education, Tribhuvan University. The study employed a qualitative case study design, and two constituent campuses taken as the research unit. Four teachers and eight students were included as participants in the study. A purposive sampling technique was used to acquire information. Data were collected by unstructured and open-ended questions, stated in verbatim form, transcribed, coded, and analyzed to generate themes. The study found that the holistic teacher involvement and care, personalized support and productive feedback meaningfully increase student stimulus, learning, and educational enhancement in master’s programs. Furthermore, the study also found that teacher engagement in master’s programs is perceived by students as multifaceted, and pedagogical awareness boosts their motivation, performance, identity, and learning, which helps in their preparation as future instructors and scholars. Effective teacher engagement in master’s programs enhances student motivation, learning, and professional development, preparing them as future scholars. This study highlights the holistic teacher involvement to increase student learning, inspiration, and professional growth. Moreover, it may be helpful to implement new engagement policies to improve the teaching learning process in higher education.